Inhibition of K+ transport through Na+, K+-ATPase by capsazepine: role of membrane span 10 of the α-subunit in the modulation of ion gating. - Yasser A Mahmmoud; Michael Shattock; Flemming Cornelius; Davor Pavlovic (PLoS ONE)
Capsazepine (CPZ) inhibits Na+,K+-ATPase-mediated K+-dependent ATP hydrolysis with no effect on Na+-ATPase activity. In this study we have investigated the functional effects of CPZ on Na+,K+-ATPase in intact cells. We have also used well established biochemical and biophysical techniques to understand how CPZ modifies the catalytic subunit of Na+,K+-ATPase. In isolated rat cardiomyocytes, CPZ abolished Na+,K+-ATPase current in the presence of extracellular K+. In contrast, CPZ stimulated pump current in the absence of extracellular K+. Similar conclusions were attained using HEK293 cells loaded with the Na+ sensitive dye Asante NaTRIUM green. Proteolytic cleavage of pig kidney Na+,K+-ATPase indicated that CPZ stabilizes ion interaction with the K+ sites. The distal part of membrane span 10 (M10) of the α-subunit was exposed to trypsin cleavage in the presence of guanidinum ions, which function as Na+ congener at the Na+ specific site. This effect of guanidinium was amplified by treatment with CPZ. Fluorescence of the membrane potential sensitive dye, oxonol VI, was measured following addition of substrates to reconstituted inside-out Na+,K+-ATPase. CPZ increased oxonol VI fluorescence in the absence of K+, reflecting increased Na+ efflux through the pump. Surprisingly, CPZ induced an ATP-independent increase in fluorescence in the presence of high extravesicular K+, likely indicating opening of an intracellular pathway selective for K+. As revealed by the recent crystal structure of the E1.AlF4-.ADP.3Na+ form of the pig kidney Na+,K+-ATPase, movements of M5 of the α-subunit, which regulate ion selectivity, are controlled by the C-terminal tail that extends from M10. We propose that movements of M10 and its cytoplasmic extension is affected by CPZ, thereby regulating ion selectivity and transport through the K+ sites in Na+,K+-ATPase.